Modulating NHC catalysis with fluorine - Rey, Yannick P.; Gilmour, Ryan (Beilstein Journal of Organic Chemistry, 2013)
Fluorination often confers a range of advantages in modulating the conformation and reactivity of small molecule organocatalysts. By strategically introducing fluorine substituents, as part of a β-fluoroamine motif, in a triazolium pre-catalyst, it was possible to modulate the behaviour of the corresponding N-heterocyclic carbene (NHC) with minimal steric alterations to the catalyst core. In this study, the effect of hydrogen to fluorine substitution was evaluated as part of a molecular editing study. X-ray crystallographic analyses of a number of derivatives are presented and the conformations are discussed. Upon deprotonation, the fluorinated triazolium salts generate catalytically active N-heterocyclic carbenes, which can then participate in the enantioselective Steglich rearrangement of oxazolyl carbonates to C-carboxyazlactones (e.r. up to 87.0:13.0).
Keywords: catalysis; enantioselectivity; fluorine; gauche effect; organo-fluorine; Steglich rearrangement

(untitled) - Zimmer, L. E.; Sparr, C.; Gilmour, R. (Angew. Chem., 2011)
Angew. Chem., Int. Ed. 2011, 50, 11860–11871. doi:10.1002/anie.201102027

Asymmetric Syntheses. More Methods and Applications - Sparr, C.; Zimmer, L. E.; Gilmour, R. (Wiley-VCH Verlag GmbH & Co, 2011)

(untitled) - Holland, M. C.; Paul, S.; Schweizer, W. B.; Bergander, K.; Mück-Lichtenfeld, C.; Lakhdar, S.; Mayr, H.; Gilmour, R. (Angew. Chem., 2013)
Angew. Chem., Int. Ed. 2013, 52, 7967–7971. doi:10.1002/anie.201301864

(untitled) - O’Hagan, D. (Chem. Soc. Rev., 2008)

(untitled) - Irwin, J. J.; Ha, T.-K.; Dunitz, J. D. (Helv. Chim. Acta, 1990)

(untitled) - Wolfe, S. (Acc. Chem. Res., 1972)

(untitled) - Huber-Wälchli, P.; Günthard, H. H. (Spectrochim. Acta, Part A, 1981)

(untitled) - Durig, J. R.; Liu, J.; Little, T. S.; Kalasinsky, V. F. (J. Phys. Chem., 1992)

(untitled) - Craig, N. C.; Chen, A.; Suh, K. H.; Klee, S.; Mellau, G. C.; Winnewisser, B. P.; Winnewisser, M. (J. Am. Chem. Soc., 1997)

(untitled) - O’Hagan, D.; Bilton, C.; Howard, J. A. K.; Knight, L.; Tozer, D. J. (J. Chem. Soc., Perkin Trans. 2, 2000)

(untitled) - Briggs, C. R. S.; O'Hagan, D.; Howard, J. A. K.; Yufit, D. S. (J. Fluorine Chem., 2003)

(untitled) - Briggs, C. R. S.; Allen, M. J.; O'Hagan, D.; Tozer, D. J.; Slawin, A. M. Z.; Goeta, A. E.; Howard, J. A. K. (Org. Biomol. Chem., 2004)

(untitled) - Sparr, C.; Schweizer, W. B.; Senn, H. M.; Gilmour, R. (Angew. Chem., 2009)
Angew. Chem., Int. Ed. 2009, 48, 3065–3068. doi:10.1002/anie.200900405

(untitled) - Bucher, C.; Sparr, C.; Schweizer, W. B.; Gilmour, R. (Chem.–Eur. J., 2009)

(untitled) - Sparr, C.; Tanzer, E.-M.; Bachmann, J.; Gilmour, R. (Synthesis, 2010)

(untitled) - Seebach, D.; Gilmour, R.; Grošelj, U.; Deniau, G.; Sparr, C.; Ebert, M.-O.; Beck, A. K.; McCusker, L. B.; Šišak, D.; Uchimaru, T. (Helv. Chim. Acta, 2010)

(untitled) - Sparr, C.; Gilmour, R. (Angew. Chem., 2010)
Angew. Chem., Int. Ed. 2010, 49, 6520–6523. doi:10.1002/anie.201003734

(untitled) - Paul, S.; Schweizer, W. B.; Ebert, M.-O.; Gilmour, R. (Organometallics, 2010)

(untitled) - Sparr, C.; Salamanova, E.; Schweizer, W. B.; Senn, H. M.; Gilmour, R. (Chem.–Eur. J., 2011)

(untitled) - Tanzer, E.-M.; Schweizer, W. B.; Ebert, M.-O.; Gilmour, R. (Chem.–Eur. J., 2012)

(untitled) - Tanzer, E.-M.; Zimmer, L. E.; Schweizer, W. B.; Gilmour, R. (Chem.–Eur. J., 2012)

(untitled) - Paul, S.; Schweizer, W. B.; Rugg, G.; Senn, H. M.; Gilmour, R. (Tetrahedron, 2013)

(untitled) - Enders, D.; Balensiefer, T. (Acc. Chem. Res., 2004)

(untitled) - Johnson, J. S. (Angew. Chem., Int. Ed., 2004)

(untitled) - Enders, D.; Niemeier, O.; Henseler, A. (Chem. Rev., 2007)

(untitled) - Dröge, T.; Glorius, F. (Angew. Chem., Int. Ed., 2010)

(untitled) - Ryan, S. J.; Candish, L.; Lupton, D. W. (Chem. Soc. Rev., 2013)

(untitled) - Nelson, D. J.; Nolan, S. P. (Chem. Soc. Rev., 2013)

(untitled) - Steglich, W.; Höfle, G. (Tetrahedron Lett., 1970)

(untitled) - Thomson, J. E.; Rix, K.; Smith, A. D. (Org. Lett., 2006)

(untitled) - Thomson, J. E.; Campbell, C. D.; Concellón, C.; Duguet, N.; Rix, K.; Slawin, A. M. Z.; Smith, A. D. (J. Org. Chem., 2008)

(untitled) - Campbell, C. D.; Duguet, N.; Gallagher, K. A.; Thomson, J. E.; Lindsay, A. G.; O’Donoghue, A. C.; Smith, A. D. (Chem. Commun., 2008)

(untitled) - Thomson, J. E.; Kyle, A. F.; Gallagher, K. A.; Lenden, P.; Concellón, C.; Morrill, L. C.; Miller, A. J.; Joannesse, C.; Slawin, A. M. Z.; Smith, A. D. (Synthesis, 2008)

(untitled) - Thomson, J. E.; Kyle, A. F.; Ling, K. B.; Smith, S. R.; Slawin, A. M. Z.; Smith, A. D. (Tetrahedron, 2010)

(untitled) - Campbell, C. D.; Collett, C. J.; Thomson, J. E.; Slawin, A. M. Z.; Smith, A. D. (Org. Biomol. Chem., 2011)

(untitled) - Campbell, C. D.; Concellón, C.; Smith, A. D. (Tetrahedron: Asymmetry, 2011)

(untitled) - DiRocco, D. A.; Oberg, K. M.; Dalton, D. M.; Rovis, T. (J. Am. Chem. Soc., 2009)

(untitled) - Sánchez-Larios, E.; Thai, K.; Bilodeau, F.; Gravel, M. (Org. Lett., 2011)

(untitled) - Um, J. M.; DiRocco, D. A.; Noey, E. L.; Rovis, T.; Houk, K. N. (J. Am. Chem. Soc., 2011)

(untitled) - DiRocco, D. A.; Noey, E. L.; Houk, K. N.; Rovis, T. (Angew. Chem., Int. Ed., 2012)

(untitled) - McIntosh, J. M.; Acquaah, S. O. (Can. J. Chem., 1988)